The Prevalence of Malformations of Cortical Development in a Pediatric Hereditary Hemorrhagic Telangiectasia Population - Palagallo, G.J.; McWilliams, S.R.; Sekarski, L.A.; Sharma, A.; Goyal, M.S.; White, A.J. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Brain AVM, cerebral abscess, and ischemic stroke are among the well known neurologic manifestations of hereditary hemorrhagic telangiectasia. However, recently reported data suggest an additional association with malformations of cortical development. The purpose of this study was to determine the prevalence of malformations of cortical development in a population of pediatric patients with hereditary hemorrhagic telangiectasia.MATERIALS AND METHODS: A retrospective review of brain MRIs from 116 pediatric patients was performed. Each patient was referred from our institution's Hereditary Hemorrhagic Telangiectasia Clinic. Each MRI included a 3D sequence, most frequently MPRAGE. The 3D sequence was evaluated by a neuroradiology fellow, with specific attention to the presence or absence of malformations of cortical development. Positive studies were subsequently reviewed by 2 attending neuroradiologists, who rendered a final diagnosis.RESULTS: Fourteen of 116 (12.1%) patients were found to have a malformation of cortical development. Among these 14, there were 12 cases of polymicrogyria and 2 cases of bifrontal periventricular nodular heterotopia.CONCLUSIONS: Pediatric patients with hereditary hemorrhagic telangiectasia have a relatively high prevalence of malformations of cortical development, typically perisylvian polymicrogyria.HHThereditary hemorrhagic telangiectasiaMCDmalformation of cortical developmentPMGpolymicrogyria